Bid’ah Perspektif Fiqih Kontemporer - Rohim, Muhammad Yusuf Nur; M, Misbahuddin; Shuhufi, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Bid'ah is a concept that is often a topic of debate in the Muslim community. The word